TRANSFORMATION OF REGIONAL POLICY: INTERPRETATION OF TERMS - Голуб’як, Н. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article defines the basic definitions to essence «decentralization», "deconcentration", "devolution" and "separatism". The author determines the main form, the advantages and disadvantages of decentralization. Recommendations of effective regional policy are formed based on the analysis of interpretative concepts.